2008
DOI: 10.1142/s0218271808012462
|View full text |Cite
|
Sign up to set email alerts
|

Collapsing Fluid With Self-Similarity of the Second Kind in 2 + 1 Gravity

Abstract: Anisotropic fluid with self-similarity of the second kind in (2 + 1)-dimensional space–times with circular symmetry is studied. By imposing the condition that the radial pressure vanishes, we show that the only allowed solutions are the ones that represent dust fluid. All such solutions to the Einstein field equations are found and their local and global properties are studied in detail. It is found that some can be interpreted as representing gravitational collapse, in which both naked singularities and black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…If we choose c = 0, we have collapse forming black hole or naked singularity (Martins et al 2008). For c = 0, y reduces to y = −α.…”
Section: Solutions Of the Einstein's Field Equationsmentioning
confidence: 99%
“…If we choose c = 0, we have collapse forming black hole or naked singularity (Martins et al 2008). For c = 0, y reduces to y = −α.…”
Section: Solutions Of the Einstein's Field Equationsmentioning
confidence: 99%
“…We further studied their local and global properties and found that some of them represent gravitational collapses of a massless scalar field, in which black holes are always formed. In another discussion we discussed an anisotropic fluid, with the same self-similarity, and showed that the existing solution is unique when the radial pressure vanishes, and it represents a collapsing dust fluid, where the final output can be either naked singularities or black holes [6].…”
Section: Introductionmentioning
confidence: 99%